Penyakit Gigi Dan Gusi Sebagai Penyebab Penyakit Jantung - Hartanto, Hamdan Ali; Meilan Arsanti; Muhammad Syarif Wicaksono (JURNAL TERAS KESEHATAN, 2024)
Tooth and gum disease is a condition that is widespread throughout the world. Examples of these diseases are caries and periodontitis. This condition is dangerous if left unchecked because infected tooth and gum microbes can migrate to other parts of the body, one of them is the cardiovascular organs. The aim of this research is to determine the manifestations of poor dental and gum disease conditions that influence the occurrence of heart or cardiovascular disease. The research method used was a literature review or literature study. Reference material was searched using secondary data through books, articles and national and international journals. Data collected relates to cavities, periodontal disease, and cardiovascular disease. Data search came from Google Scholar, Science Direct, PubMed according to keywords. The impacts of cardiovascular disease include bacterial endocarditis, angina pectoris, myocardial infarction, hypertension, atherosclerotic cardiovascular disease, heart failure, arterial fibrillation, peripheral arterial disease and other cardiovascular diseases.